Смена элиты и лидеров в либеральных демократиях - Хигли, Дж.; Пакульский, Ян (Социология: теория, методы, маркетинг, 2008)
The authors make an attempt to describe and explain the power relationships in a society. At the outset they emphazise that the way in which leaders and elites affect each other is a knotty problem in political analysis. If a shift toward more forceful leaders is occurring in liberal democracies then a comparable shift in elites must also be occurring. From the essential principles underlying Vilfredo Pareto’s, Max Weber’s and other well-known elite theories, the authors intend to explore the thesis that this is a time of increasingly forceful leaders embedded in more aggressive, tightly organized, and mutually antagonistic elites in at least some liberal democracies. Upon this basis the researchers examine elite and leadership changes that appear to be impelled by extraordinary conditions during the past twenty-five years.